Statistical investigation on equatorial pitch angle distribution of energetic electrons in Earth’s outer radiation belt during CME- and CIR-driven storms - Chakraborty, S.; Chakrabarty, D.; Reeves, G. D.; Baker, D. N.; Rae, I. J. (Frontiers in Astronomy and Space Sciences, 2022)
We present a statistical investigation (September 2012 - September 2017) of pitch angle distribution (PAD) of energetic electrons (~30 keV - 1 MeV) in the outer radiation belt (L > 3) during CME- and CIR-driven geomagnetic storms using Van Allen Probe measurements. We selected geomagnetic storms based on minimum of SYM-H being less than -50 nT and classified the storms according to their drivers. Thus, we obtained 23 CME- and 24 CIR-driven storms. During the storm intervals, pitch angle resolved electron flux measurements are obtained from the MagEIS instrument on-board Van Allen Probe-A spacecraft. We assume symmetric pitch angle distributions around 90 degree pitch angle and fit the observed PADs with Legendre polynomials after propagating them to the magnetic equator. Legendre coefficients c2 and c4, and the ratio R = |c2/c4| are used to categorize the different PAD types. To resolve the spatio-temporal distribution of PADs, these coefficients are binned in 6 L-shell bins, 13 MLT bins for 7 energy channels and 4 storm phases. We found that several hundreds of keV electrons exhibit clear dependence on local time, storm phases and storm drivers, with increased anisotropy for CME-driven storms during main and early recovery phases. On the contrary, we found that tens of keV electrons do not exhibit significant dependence on these parameters. We have discussed the different physical mechanisms responsible for the observed MLT dependent PADs and found drift-shell splitting to be the major contributor.